Killing of Microbes and Cancer by the Immune System with Three Mammalian Pore-Forming Killer Proteins - Podack, Eckhard R.; Munson, George P. (Frontiers in Immunology, 2016)
Immunology is the science of biological warfare between the defenses of our immune systems and offensive pathogenic microbes and cancers. Over the course of his scientific career Eckhard R. Podack made several seminal discoveries that elucidated key aspects of this warfare at a molecular level. When Eckhard joined the complement laboratory of Müller-Eberhard in 1974 he was fascinated by two questions: (1) What is the molecular mechanism by which complement kills invasive bacteria? and (2) Which one of the complement components is the killer molecule? Eckhard’s quest to answer these questions would lead to the discovery C9 and later, two additional pore-forming killer molecules of the immune system. Here is a brief account of how he discovered poly-C9, the pore-forming protein of complement in blood and interstitial fluids; Perforin-1, expressed by natural killer cells (NK) and cytotoxic T lymphocytes; and Perforin-2 (MPEG1), expressed by all cell types examined to date. All three killing systems are crucial for our survival and health.